SYSTEMATIC LITERATURE REVIEW (SLR) : STRATEGI GEN Z MENGELOLA KONFLIK PERTEMANAN MELALUI KOMUNIKASI DI WHATSAPP - Renza Dara Septia; Eddy Kusnadi; Jusuf Fadilah (Jurnal Komunikasi, 2025)
Digital communication has become a central element in the lives of generation Z, who have grown up amid technological advancement. WhatsApp, as one of the most popular instant messaging platforms, is widely used by Gen Z to build and maintain social relationships. However, the use of text-based communication with minimal non-verbal cues often leads to misunderstandings and conflicts, especially in the context of friendships. This study aims to systematically review the literature related to Gen Z’s communication strategies in dealing with interpersonal conflicts via WhatsApp. Using the Systematic Literature Review (SLR) method, this research analyzes 10 relevant scholarly articles published between 2020-2025. The findings indicate that Gen Z employs various communication strategies such as avoiding, compromising, accommodating, and collaborating. Symbolic communication using emoticons, stickers and message timing is a distinctive trait of Gen Z in responding to conflicts. This review highlights the need to strengthen digital emotional literacy among Gen Z to reduce conflict escalation and enhance interpersonal relationship in digital spaces